Project-Based Learning Model Improves Mathematics Outcomes of Grade IV Students: Model Pembelajaran Berbasis Proyek Meningkatkan Hasil Belajar Matematika Siswa Kelas IV - M. Ilham; Puput Wahyu Hidayat; Aprizan Aprizan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Education in elementary schools forms the foundation of human resource development, yet mathematics often becomes a major challenge due to students’ limited understanding of abstract concepts. Specific Background: At SDN 027/II Sungai Arang, nearly half of the fourth-grade students failed to reach the minimum competency score in fractions, caused by monotonous, teacher-centered methods and low engagement. Knowledge Gap: While the Indonesian Kurikulum Merdeka promotes student-centered, project-based learning, its empirical implementation in rural schools with limited resources remains underexplored. Aims: This study aimed to improve mathematics learning outcomes in fractions through the application of the Project-Based Learning (PjBL) model. Results: Conducted as Classroom Action Research in two cycles, the study revealed improvements in teacher performance (from 77.27% to 100%), student engagement (increase in highly active students from 6 to 12), and learning outcomes (mastery rising from 64% to 84%). Novelty: Unlike previous studies in better-equipped contexts, this research demonstrates the effectiveness of PjBL in a resource-limited elementary school, highlighting its adaptability and contextual relevance. Implications: The findings suggest that PjBL not only enhances conceptual mastery of fractions but also fosters critical thinking, collaboration, and motivation, thus offering a viable pedagogical strategy for advancing Kurikulum Merdeka in diverse educational settings. Highlights: PjBL improves student engagement and critical thinking. Learning outcomes in fractions increased from 64% to 84%. Effective even in resource-limited elementary schools. Keywords: Project-Based Learning, Mathematics, Fractions, Elementary Education, Learning Outcomes